Control of gastric H,K-ATPase activity by cations, voltage and intracellular pH analyzed by voltage clamp fluorometry in Xenopus oocytes. - Katharina L Dürr; Neslihan N Tavraz; Thomas Friedrich (PLoS ONE, 2012)
Whereas electrogenic partial reactions of the Na,K-ATPase have been studied in depth, much less is known about the influence of the membrane potential on the electroneutrally operating gastric H,K-ATPase. In this work, we investigated site-specifically fluorescence-labeled H,K-ATPase expressed in Xenopus oocytes by voltage clamp fluorometry to monitor the voltage-dependent distribution between E(1)P and E(2)P states and measured Rb(+) uptake under various ionic and pH conditions. The steady-state E(1)P/E(2)P distribution, as indicated by the voltage-dependent fluorescence amplitudes and the Rb(+) uptake activity were highly sensitive to small changes in intracellular pH, whereas even large extracellular pH changes affected neither the E(1)P/E(2)P distribution nor transport activity. Notably, intracellular acidification by approximately 0.5 pH units shifted V(0.5), the voltage, at which the E(1)P/E(2)P ratio is 50∶50, by -100 mV. This was paralleled by an approximately two-fold acceleration of the forward rate constant of the E(1)P→E(2)P transition and a similar increase in the rate of steady-state cation transport. The temperature dependence of Rb(+) uptake yielded an activation energy of ∼90 kJ/mol, suggesting that ion transport is rate-limited by a major conformational transition. The pronounced sensitivity towards intracellular pH suggests that proton uptake from the cytoplasmic side controls the level of phosphoenzyme entering the E(1)P→E(2)P conformational transition, thus limiting ion transport of the gastric H,K-ATPase. These findings highlight the significance of cellular mechanisms contributing to increased proton availability in the cytoplasm of gastric parietal cells. Furthermore, we show that extracellular Na(+) profoundly alters the voltage-dependent E(1)P/E(2)P distribution indicating that Na(+) ions can act as surrogates for protons regarding the E(2)P→E(1)P transition. The complexity of the intra- and extracellular cation effects can be rationalized by a kinetic model suggesting that cations reach the binding sites through a rather high-field intra- and a rather low-field extracellular access channel, with fractional electrical distances of ∼0.5 and ∼0.2, respectively.